THE EFFECT OF HOST PLANT REPLACEMENT ON THE GENETIC STRUCTURE OF THE KRASNODAR GREENBUG SCHIZAPHIS GRAMINUM RONDANI (HOMOPTERA, APHIDIDAE) POPULATION - E. E. Radchenko; T. L. Kuznetsova (Труды по прикладной ботанике, генетике и селекции)
Characteristics of the new malting spring barley cultivar ‘Omsky 100’ are presented. This cultivar, bred at the Siberian Research As a result of studying the Krasnodar Schizaphis graminum population, a high level of the insect’s overall and seasonal variability in its virulence to sorghum resistance genes was detected. The greenbug population feeding on sorghum was shown to be labile in virulence to barley accessions as well. The selection of S. graminum genotypes specifically adapted to host plant species was observed. During the reproduction of the insect on barley plants, the individuals without “redundant” genes of virulence to sorghum had an advantage in competition. Replacement of the host led to rapid accumulation of clones virulent to the sorghum resistance genes Sgr1 - Sgr4 and Sgr12.